Effects of high potencies of tumour necrosis factor alpha on H2O2 production in cultured neuroblastoma cells by enhanced luminol-dependent chemiluminescence (ECL) - Carmine, T.C. (British Homeopathic Journal, 1997)
The effects of homoeopathic high dilutions of cytokine TNFα on H2O2 production of SK-N-SH neuroblastoma cells were studied. H2O2 was measured using a highly sensitive chemiluminescence method (ECL) based on chemical enhancement of luminol oxidation in the presence of peroxidase and H2O2. The dose-effect relationship between TNFα and H2O2 production of SK-N-SH cells was established over the whole range from 200 ng/ml of TNFα to 100x. Interpolation yielded a waveshaped curve (phase length 5–8) which appeared to ‘ride’ on a wave-shaped 10th order regression curve (phase length ∼ 35). The effects of TNFα 100x on H2O2 production were highly significant (p < 0.002). Elevation of H2O2 production compared to controls was repeatedly seen following incubation of SK-N-SH cells in the presence of TNFα 100x. These results suggest that the chemiluminescence method used is suitable to demonstrate and investigate further the influence of homoeopathic high potencies on biological systems.
Keywords: Experimental homoeopathy; High potencies; Neuroblastoma; TNFα; Hydrogen peroxide; Enhanced luminol-dependent chemiluminescence (ECL)